2021
DOI: 10.1200/jco.20.03458
|View full text |Cite
|
Sign up to set email alerts
|

Humanized CD19-Targeted Chimeric Antigen Receptor (CAR) T Cells in CAR-Naive and CAR-Exposed Children and Young Adults With Relapsed or Refractory Acute Lymphoblastic Leukemia

Abstract: PURPOSE CD19-targeted chimeric antigen receptor (CAR)–modified T cells demonstrate unprecedented responses in B-cell acute lymphoblastic leukemia (B-ALL); however, relapse remains a substantial challenge. Short CAR T-cell persistence contributes to this risk; therefore, strategies to improve persistence are needed. METHODS We conducted a pilot clinical trial of a humanized CD19 CAR T-cell product (huCART19) in children and young adults with relapsed or refractory B-ALL (n = 72) or B-lymphoblastic lymphoma (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(64 citation statements)
references
References 25 publications
1
63
0
Order By: Relevance
“…34 Treatment with investigational humanized CD19-specific CAR T cells is an option for relapsed patients but is not widely available. 35 Reinfusion of tisagenlecleucel when additional doses are manufactured is under clinical investigation (NCT04225676) but the utility of this approach may be ineffective if the patient has already established an anti-CAR immunologic response. 36 In summary, CD19-specific CAR T cells for R/R EM disease offers a beneficial, effective option with similar toxicity and OS rates when compared to patients with BM only disease.…”
Section: Discussionmentioning
confidence: 99%
“…34 Treatment with investigational humanized CD19-specific CAR T cells is an option for relapsed patients but is not widely available. 35 Reinfusion of tisagenlecleucel when additional doses are manufactured is under clinical investigation (NCT04225676) but the utility of this approach may be ineffective if the patient has already established an anti-CAR immunologic response. 36 In summary, CD19-specific CAR T cells for R/R EM disease offers a beneficial, effective option with similar toxicity and OS rates when compared to patients with BM only disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although this CR rate was lower than those obtained in patients firstly accepted mCD19 CAR-T in which CR rates reached 81–90% [ 1 4 ], the therapeutic efficiency of hCD19 CAR-T cells for these heavily treated patients who had no more treatment options was encouraging. A recent study also reported that the humanized CD19 CAR-T produced initial responses in 64% of patients treated for CD19+ relapse, early B-cell recovery, or nonresponse after prior murine CAR-T cells [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that one patient relapsing after mCD19 CAR-T did not respond to a secondary infusion of mCD19 CAR-T cells but obtained CR following hCD19 CAR-T [ 8 ]; and 4 of 5 patients who had received previous mCD19 CAR-T and relapsed with CD19 + B lymphoblastic cells achieved CR by treatment with humanized selective CD19 CAR-T [ 9 ]. Very recently, while this paper was in preparation, a new study showed that, in 33 childhood and young adult B-ALL patients with prior mCD19 CAR exposure (CD19+ relapse, n = 15; B-cell recovery, n = 16; no response to prior CAR-T cells, n = 2), the overall response rate at 1 month after humanized CD19 CAR-T cell infusion was 64% [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…To reduce ICANS and CRS and to diminish T-cell exhaustion, Ghorashian et al ( 25 ) designed and investigated a low-affinity CD19.scFv (CAT CD19 CAR-T, Figure 1A ), as discussed above. Lastly, the strategy of humanised scFvs is being pursued to avoid the activation of the patient's immune system against murine parts of the CAR and subsequent rejection of the cells and short-term persistence ( 109 ).…”
Section: Factors Influencing Long-term Efficacymentioning
confidence: 99%
“…Another approach reported from the same group at the CHOP/University of Pennsylvania ( 109 ) is the infusion of a humanised CAR construct (huCART19 or CTL119) in attempt to overcome the possibility of an anti-murine immune response. In a pilot trial (NCT02374333), 33 R/R BCP-ALL patients with either partial or no response to prior tisagenlecleucel, CD19 + relapse or early B-cell recovery (defined as occurring within 6 months of prior CAR T-cell infusion), were infused with huCART19 ( 109 ). The ORR 1 month after infusion was 64% in the re-treatment cohort.…”
Section: Strategies For Preventing Leukaemic Relapse Post Car-tmentioning
confidence: 99%